Assembly of complex viruses exemplified by a halophilic euryarchaeal virus - Luigi De Colibus (Nature Portfolio, 2019)
Here, the authors present the cryo-EM structure of the archaeal virus SH1 at 3.8 Å resolution and show how the major capsid proteins assemble into hetero-hexamers, providing insights into the assembly process of this and related PRD1-adeno lineage viruses.